Planning Of The Operational Bureau Of The East Java Police In Securing The 2024 Simultaneous Regional Head Election - edista_indiswari_artamefia; Rosyidatuzahro Anisykurlillah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Operations Bureau is a work unit (satker) at the Regional Police level, specifically in the East Java region, which has an important role in planning security for police force members. The research approach uses a qualitative descriptive method with data collection through interviews, direct observation, and document studies. This study aims to determine the Security Planning for the 2024 Simultaneous Regional Elections, which was carried out because it required the assistance of security forces during the 2024 Simultaneous Regional Elections. In this context, the Regional Head Election (Pilkada) is an important mechanism for community participation in decision-making. However, security challenges, such as political vulnerability, violations, and possible riots are a major concern, especially in East Java Province. News emerged during the 2024 Simultaneous Regional Elections when there was riots in the Madura Raya area. The results of the study show that the Operations Bureau has taken proactive steps to deal with potential vulnerabilities, including the addition of security personnel in vulnerable areas. Although planning has covered various aspects, there are shortcomings in developing alternatives. This study emphasizes the importance of structured and responsive planning to create safe and conducive conditions during the Pilkada, and to ensure that the democratic process runs smoothly. Keywords: East Java Regional Police Operations Bureau, Pilkada, Planning, Security.